The association between the CUN-BAE index and depression mediated by SIRI: A large cross-sectional study - Muxi Li; Yazhi Qi; Mengru Cao; Hongjun Lou; Wei Teng; Long Wang (PLoS ONE, 2025)
Background Depression is a common global mood disorder problem and one of the major disabling factors. The Clínica Universidad de Navarra-Body Adiposity Estimator (CUN-BAE) index is an important composite indicator for measuring fat content in the body. Our goal is to find out the relationship between the CUN-BAE index and depression, as well as the mediating effect of the Systemic Inflammatory Response Index (SIRI) between the two. Methods All participants aged ≥ 20 from the 2005–2020 cycles of the NHANES in the US were included in the research. To assess the relationships between CUN-BAE and SIRI and depression, we used weighted multivariable logistic regression models. Potential nonlinearity was examined using restricted cubic splines (RCS) regression models. We performed mediation analysis with 1000 bootstrap replicates to evaluate the mediating function of SIRI in the relationship of CUN-BAE and depression. Results 31,592 participants were examined for the statistical analysis, of whom 28,825 were classified into the non-depression group and 2,767 were identified as belonging to depression group. Individuals in the depression group were more probable to be female and to have diabetes and hypertension, and higher SIRI and CUN-BAE levels. An incremental rise of one unit in CUN-BAE was connected to a 2% elevation in the odds of developing depression (OR = 1.02; 95% CI: 1.01–1.03; P < 0.001). The regression analysis revealed a statistically significant non-linear positive relationship between CUN-BAE levels and depressive status ( P for non-linearity = 0.005), alongside a J-shaped curve characterizing the association between log-transformed SIRI and depression ( P for non-linearity = 0.007). The AUC of CUN-BAE for predicting depression was 0.60(0.59,0.61). With a 3% mediating effect, SIRI functioned as a partial mediator in the pathway linking CUN-BAE levels to depression. Conclusions The level of the CUN-BAE index might serve as a potential index for assessing an individual’s risk of developing depression. Monitoring body fat and inflammation levels might be useful for early detection of those who are potentially at risk for depression.